Paradygmat społeczeństwa opartego na wiedzy w warunkach nowej ekonomii: Knowledge based society paradigm in conditions of the new economy - Skrzypek, Adam (Management and Administration Journal, 2021)
The new economy paradigm reflects upon how modern economies are being trasformed in response to the impact of information technologies. The new economy stresses the crucial role information plays and the importance of the information sector in the economy. New economy lays foundations for electronic use of knowledege and information. A number of factors contributed to the evolution of the new economy. Namely, higher level of education in society, the process of internalization of economies and the development of information and communication technologies. The new economy triggers fiercer competition. The new economy's three pillars are education and training, ICT systems and knowledge management. In conditions of the new economy, a new management paradigm emerges. It has four components: focus, first, fast, flexible. The new management paradigm's guidelines are value creation, quality, response, agility, innovation, integration and teamwork.